2023
DOI: 10.5712/rbmfc18(45)3347
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à infeção pelo vírus da dengue

Abstract: Introdução: A dengue é uma doença infecciosa endêmica em regiões tropicais e subtropicais. Para organizar uma rede assistência de saúde e garantir medidas preventivas, manejo clínico adequado, é necessário conhecer os fatores associadas aos casos de dengue. Objetivo: Analisar os fatores associados à infecção pelo vírus da dengue de indivíduos notificados no sistema de vigilância em saúde. Métodos: Estudo transversal de dados secundários de casos de suspeitos de dengue notificados no Sistema Nacional de Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The former consists in a low complexity blood test, however the detection interval must be respected, recommendations are testing after six days of symptoms 18 . Despite that, a cross-sectional study conducted in São Mateus county, state of Espítiro Samto, found that dengue cases were confirmed mostly by clinical-epidemiological criterion and only 27,7% by blood test 19 . In Alagoas state, clinical-epidemiological confirmation were 70,93% and blood tests only 10,70% 20 .…”
Section: Discussionmentioning
confidence: 92%
“…The former consists in a low complexity blood test, however the detection interval must be respected, recommendations are testing after six days of symptoms 18 . Despite that, a cross-sectional study conducted in São Mateus county, state of Espítiro Samto, found that dengue cases were confirmed mostly by clinical-epidemiological criterion and only 27,7% by blood test 19 . In Alagoas state, clinical-epidemiological confirmation were 70,93% and blood tests only 10,70% 20 .…”
Section: Discussionmentioning
confidence: 92%